Biophysical Characterization and Membrane Interaction of the Two Fusion Loops of Glycoprotein B from Herpes Simplex Type I Virus - Falanga, Annarita; Tarallo, Rossella; Vitiello, Giuseppe; Vitiello, Mariateresa; Perillo, Emiliana; Cantisani, Marco; D'Errico, Gerardino; Galdiero, Massimiliano; Galdiero, Stefania (PLOS ONE, 2012)
The molecular mechanism of entry of herpesviruses requires a multicomponent fusion system. Cell invasion by Herpes simplex virus (HSV) requires four virally encoded glycoproteins: namely gD, gB and gH/gL. The role of gB has remained elusive until recently when the crystal structure of HSV-1 gB became available and the fusion potential of gB was clearly demonstrated. Although much information on gB structure/function relationship has been gathered in recent years, the elucidation of the nature of the fine interactions between gB fusion loops and the membrane bilayer may help to understand the precise molecular mechanism behind herpesvirus-host cell membrane fusion. Here, we report the first biophysical study on the two fusion peptides of gB, with a particular focus on the effects determined by both peptides on lipid bilayers of various compositions. The two fusion loops constitute a structural subdomain wherein key hydrophobic amino acids form a ridge that is supported on both sides by charged residues. When used together the two fusion loops have the ability to significantly destabilize the target membrane bilayer, notwithstanding their low bilayer penetration when used separately. These data support the model of gB fusion loops insertion into cholesterol enriched membranes.